Chondroitin sulfate activates B cells in vitro, expands CD138+ cells in vivo, and interferes with established humoral immune responses. Issue 1 (20th February 2014) - Brühl, Hilke; Cihak, Josef; Goebel, Nicole; Talke, Yvonne; Renner, Kerstin; Hermann, Fabian; Rodriguez‐Gomez, Manuel; Reich, Barbara; Plachý, Jîŕi; Stangassinger, Manfred; Mack, Matthias
Abstract : Chondroitin sulfate activates B cells in a BTK‐ and Syk‐dependent manner, and suppresses established humoral immune responses by interfering with antigen specific plasma cells. Abstract : Glycosaminoglycans have anti‐inflammatory properties and interact with a variety of soluble and membrane‐bound molecules. Little is known about their effects on B cells and humoral immune responses. We show that CS but not dextran or other glycosaminoglycans induces a pronounced proliferation of B cells in vitro compared with TLR4 or TLR9 ligands. With the use of inhibitors and KO mice, we demonstrate that this proliferation is mediated by the tyrosine kinases BTK and Syk but independent of CD44. Antibodies against Ig‐α or Ig‐β completely block CS‐induced B cell proliferation. Injection of CS in mice for 4–5 days expands B cells in the spleen and results in a marked increase of CD138 + cells in the spleen that is dependent on BTK but independent of CD4 + T cells. Long‐term treatment with CS for 14 days also increases CD138 + cells in the bone marrow. When mice were immunized with APC or collagen and treated with CS for up to 14 days during primary or after secondary immune responses, antigen‐specific humoral immune responses and antigen‐specific CD138 + plasma cells in the bone marrow were reduced significantly. These data show that CD138 + cells, induced by treatment with CS, migrate into the bone marrow and may displace other antigen‐specific plasma cells. Overall, CS is able to interfere markedly with primary and fully established humoral immune responses in mice.